Pengaruh CR, DER, ROE Dan EPS Terhadap Harga Saham Pada Perusahaan Mining Atau Pertambangan - Zulfa Fitria; Dedi Suselo (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2022)
This study aims to analyze the effect of the Current Ratio (CR), Debt to Equity Ratio (DER), Return On Equity (ROE) and Earning Per Share (EPS) either partially or simultaneously on stock prices in mining or mining companies listed on the Indonesia Stock Exchange. The period in this study was carried out for 4 years, namely from 2017 to 2020. The type of data used in this research is quantitative data. The data source used is secondary data taken from the annual financial statements of mining companies from 2017 to 2020 obtained from the Indonesia Stock Exchange (www.IDX.co.id). The research population is all mining companies listed on the Indonesia Stock Exchange from 2017 to 2020, namely 47 mining companies. The sample in this study used a purposive sampling technique and 9 companies as the object of research. The analytical method used is multiple linear regression. Based on the results of data analysis from this study, it shows that the variables Current Ratio, Debt to Equity Ratio, Return On Equity and Earning Per Share simultaneously have a significant effect on stock prices resulting from the f test and t-test.